Investasi Cryptocurrencies. Bertahan dengan Kerugian Cryptocurrencies? - Kiky, Andreas; Saputera, David (www.bsi.ac.id, 2023)
Holding the loss without reason is one of the behavioural biases which are very common to be found in investment. Investment is also entering a new era of modern and sophisticated assets. One of these assets is known as cryptocurrencies. This article is written to detect whether the disposition effect is occurring to cryptocurrency investors and whether they are holding the loss. The disposition effect in this research was measured as respondents' perception of whether they sold the winning assets too fast and kept the failure in the long run. The result from this research is disposition effect was indeed found in descriptive statistics but failed to confirm the influence of independent variables on the disposition effect using the linear regression method. There is no effect of financial literacy, overconfidence, regret aversion, and risk tolerance on the perceptional disposition effect, which the emotional factor of loss aversion might cause. This will cause an individual to be reluctant to realize the loss in the hope the asset will return to the initial purchasing price. Further investigation will be the future area for developing research about the disposition effect. Interestingly, this research also found the literacy score of the respondents is deficient, but they are very confident in investing in the most volatile asset, such as cryptocurrencies. This research has several limitations, such as the sample being relatively similar in financial literacy, so selecting a wide range (heterogenous), sample in future research is crucial. Another improvement is in methodology, and perhaps an experimental approach could be a promising field in the study of behavioural bias in the future.